Disentangling the Possible Drivers of Indri indri Microbiome: A Threatened Lemur Species of Madagascar - Correa, Federico; Torti, Valeria; Spiezio, Caterina; Checcucci, Alice; Modesto, Monica; Borruso, Luigimaria; Cavani, Luciano; Mimmo, Tanja; Cesco, Stefano; Luise, Diana; Randrianarison, Rose M.; Gamba, Marco; et al. (Frontiers in Microbiology, 2021)
Research on the gut microbiome may help with increasing our understanding of primate health with species’ ecology, evolution and behavior. In particular, microbiome-related information has the potential to clarify ecology issues, providing knowledge in support of wild primates conservation and their associated habitats. Indri (Indri indri) is the largest extant living lemur of Madagascar. This species is classified as 'critically endangered' by the IUCN Red List of Threatened Species, representing one of the world's 25 most endangered primates. Indris diet is mainly folivorous, but these primates frequently and voluntarily engage in geophagy. Indris have never been successfully bred under human care, suggesting that some behavioral and/or ecological factors are still not considered from the ex-situ conservation protocols. Here, we explored gut microbiome composition of 18 indris belonging to 5 different family groups. The most represented phyla were Proteobacteria 40.1 ±9.5%, Bacteroidetes 28.7 ±2.8%, Synergistetes 16.7 ±4.5% and Firmicutes 11.1 ±1.9%. Further, our results revealed that bacterial alpha and beta diversity were influenced by indri family group and sex. In addition, we investigated the chemical composition of geophagic soil to explore the possible ecological value of soil as a nutrient supply. The quite acidic pH and high levels of secondary oxide-hydroxides of the soils could play a role in the folivorous diet's gut detoxification activity. In addition, the high contents of iron and manganese found the soils could act as micronutrients in the indris' diet. Nevertheless, the concentration of a few elements (i.e. calcium, sulfur, boron, nickel, sodium and chromium) was higher in non-geophagic than in geophagic soils. In conclusion, the data presented herein provide a baseline for outlining some possible drivers responsible for the gut microbiome diversity in indris, thus laying the foundations for developing further strategies involved in indris’ conservation.